2022
DOI: 10.3389/fgene.2022.922712
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of mRNA-single nucleotide polymorphism-microRNA interaction network to identify biomarkers associated with prostate cancer

Abstract: Background: Prostate cancer is one of the most common malignancies among men worldwide currently. However, specific mechanisms of prostate cancer were still not fully understood due to lack of integrated molecular analyses. We performed this study to establish an mRNA-single nucleotide polymorphism (SNP)-microRNA (miRNA) interaction network by comprehensive bioinformatics analysis, and search for novel biomarkers for prostate cancer.Materials and methods: mRNA, miRNA, and SNP data were acquired from Gene Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…miRNAs are small non-coding RNAs and are part of the epigenetic machinery that can regulate the expression of genes; therefore, increasingly altered mechanisms are identified due to the malfunction of these miRNAs, for example, it has been observed that several miRNAs dysregulated in PCa, are related to the regulatory T cell marker FOXP3, suggesting a relationship between immune cells, miRNAs and PCa (16). Therefore, the identification of dysregulated miRNAs could have implications both in understanding the pathology and in identifying possible targets for the detection, prognosis and treatment of various cancers (17,18). The dysregulation of the expression of a miRNA can be due to mutations in its coding genes or in their regulatory regions; for example, SNPs in miR-146a and in miR-100 have been identified that act as a factor of bad and an improved prognosis in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are small non-coding RNAs and are part of the epigenetic machinery that can regulate the expression of genes; therefore, increasingly altered mechanisms are identified due to the malfunction of these miRNAs, for example, it has been observed that several miRNAs dysregulated in PCa, are related to the regulatory T cell marker FOXP3, suggesting a relationship between immune cells, miRNAs and PCa (16). Therefore, the identification of dysregulated miRNAs could have implications both in understanding the pathology and in identifying possible targets for the detection, prognosis and treatment of various cancers (17,18). The dysregulation of the expression of a miRNA can be due to mutations in its coding genes or in their regulatory regions; for example, SNPs in miR-146a and in miR-100 have been identified that act as a factor of bad and an improved prognosis in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations have been identified in both miRNA genes and their target genes, and these variations have been associated with a wide range of human diseases. Meanwhile, there is mounting evidence supporting the idea that dysregulated miRNAs play critical roles in tumorigenesis [18,19]. In CRC, several miRNAs have been identified to modulate cell proliferation, migration, apoptosis, and response to radiation in both CRC cells and patient samples.…”
Section: Introductionmentioning
confidence: 99%